2003
DOI: 10.1046/j.1460-9568.2003.02745.x
|View full text |Cite
|
Sign up to set email alerts
|

A double dissociation between serial reaction time and radial maze performance in rats subjected to 192 IgG‐saporin lesions of the nucleus basalis and/or the septal region

Abstract: The cholinergic basal forebrain has been implicated in aspects of cognitive function including memory and attention, but the precise contribution of its major components, the basalocortical and the septohippocampal systems, remains unclear. Rats were subjected to lesions of either the nucleus basalis magnocellularis (Basalis), the medial septum/vertical limb of the diagonal band of Broca (Septum), or both nuclei (Basalis + Septum), using the selective cholinotoxin 192 IgG-saporin. Cognitive performance was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 100 publications
(166 reference statements)
12
81
1
Order By: Relevance
“…The findings are also compatible with additional effects of DA on the regulation of basal forebrain cholinergic neurons (Sarter and Bruno, 1999), possibly in a way that diminishes the well-established influence of cortically projecting cholinergic neurons on visual attentional processing (Voytko et al, 1994;Himmelheber et al, 2001;McGaughy et al, 2002;Risbrough et al, 2002;Dalley et al, 2001Dalley et al, , 2004. Indeed, it is noteworthy that the main effects of selective lesions of the basal forebrain cortical cholinergic system on the 5-CSRTT are reduced response accuracy and increased omissions (McGaughy et al, 2002;Risbrough et al, 2002;Lehmann et al, 2003;Dalley et al, 2004), effects that bear close resemblance to the present study.…”
Section: Neural Basis Of Amphetamine-induced Attentional Dysfunctionsupporting
confidence: 68%
“…The findings are also compatible with additional effects of DA on the regulation of basal forebrain cholinergic neurons (Sarter and Bruno, 1999), possibly in a way that diminishes the well-established influence of cortically projecting cholinergic neurons on visual attentional processing (Voytko et al, 1994;Himmelheber et al, 2001;McGaughy et al, 2002;Risbrough et al, 2002;Dalley et al, 2001Dalley et al, , 2004. Indeed, it is noteworthy that the main effects of selective lesions of the basal forebrain cortical cholinergic system on the 5-CSRTT are reduced response accuracy and increased omissions (McGaughy et al, 2002;Risbrough et al, 2002;Lehmann et al, 2003;Dalley et al, 2004), effects that bear close resemblance to the present study.…”
Section: Neural Basis Of Amphetamine-induced Attentional Dysfunctionsupporting
confidence: 68%
“…Given the quite different natures of the behavioral tasks and the sensitizing regimens of amphetamine it is difficult to make direct comparisons between our study and those of Sarter and co-workers. However, it is interesting that several studies (Lehmann et al, 2003;Muir et al, 1994Muir et al, , 1993 have shown that cortical acetylcholine depletion impairs attentional performance in the 5-choice serial reaction time test in a manner similar to amphetamine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Subtle effects of ACh on memory could be mediated by changes in attentional processing, and this may help explain some of the inconsistencies. Lesions of corticopetal cholinergic projections (from the NBM) also often impair performance on a variety of attentional tasks (McGaughy et al 1996(McGaughy et al , 2002Lehmann et al 2003) without substantially affecting memory (e.g., Baxter et al 1995;Dornan et al 1996;Galani et al 2002). These findings indicate that impairments in attention following basal forebrain cholinergic lesions must exert relatively circumscribed effects on the overall efficiency of cognitive processing in order for learning and memory to proceed in the presence of impaired attentional processing.…”
Section: Learning and Memory 13mentioning
confidence: 97%
“…For example, rats may use egocentric (body movement) cues, path integration, orientation to single visual cues, spatial maps, or any combination thereof to solve such problems (Whishaw et al 1995;Dudchenko et al 1997;Martin et al 1997;Dudchenko 2001). Two studies have suggested that lesions of MS/ VDB cholinergic neurons bias rats away from using an allocentric (place) strategy to solve a radial arm maze (Janis et al 1998;Lehmann et al 2003), although other studies have found that rats with these lesions are able to use such strategies in the crossmaze (Cahill and Baxter 2001) or water maze . Examination of particular strategies used by animals to solve spatial problems might represent a fruitful avenue of investigation, as selective neurochemical lesions may be able to reveal how spatial cognition is fractionated within the hippocampus.…”
Section: Learning and Memory 13mentioning
confidence: 99%
See 1 more Smart Citation